(untitled) (Journal of Science and Technology, 2016)
In this work, the performance of a deep – submicron áµŸ doped MOSFET has been evaluated in terms of its conventional counterpart using 2 – D stimulation. The comparison was based on the scaling law relationships reported in the literature and relative data is given for subthreshold leakage currents, DIBL, speed and cut – off frequencies. A performance figure of merit indicates the conventional device out performs that performs that of the áµŸdoped MOSFET by 30%.